Description of Learning Implementation in Entrepreneurship Courses Package C Program at PKBM Farilla Ilmi Padang - Yolanda, Yolanda; Syuraini, Syuraini (SAINTIS Publishing, 2019)
This study was motivated by the success of the Package C education program in PKBM Farilla Ilmi Kota Padang, as evidenced by the high percentage of attendance of the learning population and satisfying learning citizen test scores. The researcher suspected that the cause of the success of the Package C program was because of the implementation of learning, one of which was seen from Entrepreneurship subjects. This type of study is a quantitative descriptive study. The population in this study were 60 people who studied the Package C program. The sampling technique used was classified as a random sampling of 30 people. The technique of collecting data uses a questionnaire. While the data collection tool uses a list of statements (questionnaires). The data analysis technique uses the percentage formula. The results of the study show that the implementation of learning in the Entrepreneurship subjects in the Package C education program, seen from the learning strategies used by tutors is classified as good.